RELATIONSHIP FAMILY SUPPORT WITH INTERDIALYTIC WEIGHT GAIN (IDWG) VALUE IN HEMODIALYSIS PATIENTS IN RADEN MATTAHER JAMBI HOSPITAL - Nofrida Saswati; Dasuki Dasuki; Suratni Suratni (Poltekkes Kemenkes Jambi, 2020)
Background: Chronic kidney failure in the final stages requires permanent kidney replacement in the form of hemodialysis. Complications that often occur in clients who undergo hemodialysis, one of which is edema due to excessive fluid intake called IDWG increase. To overcome the increase in IDWG family support is needed. This study aims to determine the relationship of family support with IDWG values ​​in the hemodialysis room at Raden Mattaher Jambi Hospital in 2018. Method: This research is a quantitative cross sectional design study. The population in this study were all patients with CRF who underwent hemodialysis at Raden Mattaher Hospital in Jambi totaling 84 patients and sampling was done using a total sampling technique of 50 patients according to inclusion criteria. The analysis in this study is Univariate and Bivariate using the Chi-Square test, this study uses a questionnaire sheet. Results: There were 28 (56.0%) respondents had moderate IDWG values, 31 (62%) respondents had good family support. There is a relationship between family support and IDWG in the hemodialysis room at Raden Mattaher Jambi Hospital (P-Value = 0.001). Conclusion: There is a relationship between family support and IDWG values ​​in the hemodialysis room at Raden Mattaher Jambi Hospital. It is expected that nurses will further enhance the provision of counseling to the patient's family to accompany and provide support in undergoing hemodialysis.